Lipopolysaccharide-induced testicular dysfunction and epididymitis in mice: a critical role of tumor necrosis factor alpha. Issue 3 (6th November 2018) - Wang, Fei; Liu, Weihua; Jiang, Qian; Gong, Maolei; Chen, Ran; Wu, Han; Han, Ruiqin; Chen, Yongmei; Han, Daishu
Abstract: Systemic inflammation may impair male fertility, and its underlying mechanisms remain poorly understood. The present study investigates the effect of lipopolysaccharide (LPS)-induced systemic inflammation on the testis and epididymis in mice. Intraperitoneal injection of LPS significantly impaired testicular functions, including testosterone production, spermatogenesis, and blood–testis barrier permeability. The epididymitis characterized by leukocyte infiltration and fibrosis was observed in the cauda epididymis after LPS injection. LPS-induced testicular dysfunction and epididymitis were abolished in tumor necrosis factor alpha ( Tnfa ) knockout mice. Pomalidomide, a TNFA inhibitor, blocked the detrimental effects of LPS on the testis and epididymis. The results indicate that LPS-induced systemic inflammation impairs male fertility through TNFA production, suggesting that the intervention on TNFA production would be considered for the prevention and treatment of inflammatory impairment of male fertility. Abstract : LPS-induced systemic inflammation leads to testicular dysfunction and epididymitis through TNFA production in mice.